Specific Features of Patients Under 40 Years Old With Small-to-Medium-Sized Arterial Deterioration - Matsubara, Kazuyoshi; Fukuhara, Natsumi; Hoshina, Katsuyuki; Miyahara, Kazuhiro; Suhara, Masamitsu; Taniguchi, Ryosuke; Matsukura, Mitsuru; Takayama, Toshio (Frontiers in Surgery, 2022)
Background Arterial deterioration is mostly caused by atherosclerosis, which progresses with age. However, we have observed serious backgrounds or etiologies in younger patients with nonatherosclerotic diseases and deterioration of small-to-medium-sized arterial lesions. Therefore, we aimed to identify the specific features of patients aged <40 years with deterioration of small-to-medium-sized arteries. Methods We selected patients who were admitted to our department from 1995 to 2019 with deterioration of small-to-medium-sized arteries (aneurysms, dissection, rupture, or arterial injury/damage) and focused on the cohort aged <40 years. We examined the backgrounds or etiologies of the patients including genetic and inflammatory diseases, which might have caused the arterial deterioration. Results Consequently, more than half (54.1%) of the patients aged <40 years had nonatherosclerotic comorbid diseases. However, the number of deteriorated arterial lesions was higher in patients aged <40 years than in patients aged ≥40 years (3.13 vs. 1.33 lesion/patient; P = 0.011). Furthermore, the data analysis of patients with multiple arterial lesions (≥3) revealed that the younger population tended to have more specific backgrounds or etiologies, notably Ehlers-Danlos syndrome and Behçet's disease. There were no differences in the all-cause mortality and cardiovascular disease-related mortality between patients aged <40 and ≥40 years (P = 0.89 and 0.29, respectively) Conclusions Over 50% of patients aged <40 years with deterioration of small-to-medium-sized arteries had nonatherosclerotic, specific clinical backgrounds or etiologies, including genetic and inflammatory diseases. In addition, they exhibited more arterial lesions than older patients.